6C.02: EXOME SEQUENCING IN SEVEN FAMILIES AND GENE-BASED ASSOCIATION STUDIES SUPPORT GENETIC HETEROGENEITY AND SUGGEST POSSIBLE CANDIDATES FOR FIBROMUSCULAR DYSPLASIA. (June 2015) - Kiando, S.; Plouin, P.F.; Barlassina, M.C.; Cusi, D.; Galan, P.; Lathrop, M.; Jeunemaitre, X.; Bouatia-Naji, N.
Abstract : Objective: Fibromuscular dysplasia (FMD) is a group of nonatherosclerotic and noninflammatory vascular disease leading to stenosis, aneurysm and dissection of medium-sized arteries, mainly renal arteries and carotids. FMD occurs predominantly in females with a prevalence of ∼ 4/1000 for clinical forms that cause hypertension, renal ischemia or stroke. The pathogenesis of FMD is unknown and a genetic origin is suspected given its demonstrated familial aggregation. Our study objective is to identify genetic variants involved in FMD aetiology. Design and method: We performed whole exome sequencing (WES) in 16 FMD cases from 7 families (5 sibpairs and 2 sibtrios). Coding variants in 3, 971 genes confidently called (read depth > 20X) were prioritized on their frequency (allele frequency < 0.01) and in silico predicted functionality. Results: No gene harbored variants that were shared among all affected members of at least 3 out of 7 families. Rare coding variants from 16 known causative genes of vascular and connective tissue syndromes (e.g. FBN1, TGFB2 and COL3A1) were excluded as causative in these families. Genes with at least 4 rare coding variants identified in the 16 patients were followed-up using genotyping data by exome chip (Illumina HumanExome-12v1_A Beadchip) from 249 FMD unrelated cases and 689 controls. Gene-based association of rare variants using SKAT-O showed nominal significant (P < 0.05) association with multifocal FMD (N = 164) for OBSCN encoding a sarcomeric protein (P = 0.003), DYNC2H1 encoding a cytoplasmic dynein (P = 0.02) and RNF213 previously associated with Moyamoya disease (P = 0.01). Conclusions: Our study reports data from the first WES investigation conducted for familial forms of FMD. It supports strong genetic heterogeneity for FMD and excludes the implication of several known vascular diseases causative genes in familial FMD etiology. We provide some evidence of association with multifocal FMD for OBSCN, DYNC2H1 and RNF213, though these findings need to be confirmed in independent cohorts. More powerful WES and association studies (e.g GWAS) will better decipher the genetic basis of FMD.